The Relationship between Federal Budget Amendments and Local Electoral Power - Sergio Firpo; Vladimir Ponczek; Viviane Sanfelice (Institute for the Study of Labor (IZA), 2014)
The objectives of this paper are twofold. First, we investigate whether politicians use resources from the federal budget as a strategy to maintain and expand their political capital. Second, we examine whether such a strategy is rewarded by voters who elect politicians who assist their municipalities through federal expenditures. The main contribution of this study is its illustration of how the use of fiscal policy affects the local political power of legislators in Brazil. We focus on the geographical distribution of votes received by politicians within their electoral districts instead of only examining the final outcomes of reelection efforts. Our findings indicate that politicians tend to favor municipalities that were important to their elections and that voters support candidates who have brought resources to their localities. However, given that Brazil uses a party-open-list proportional representation system for congressional elections, influencing the behavior of voters through amendments is not sufficient to increase a candidate's chances of winning reelection.
Keywords: H7; 330; voter's preference; pork barrel; politician's strategies; electoral power